Thalidomide - a chance for use in modern disease treatment? - Turek, Marta; Szlążek, Julia; Zagalska, Michalina; Ząbek, Adam Jan; Kuźniar, Jakub Paweł; Chrzanowska, Emilia Gabriela; Tamborski, Tomasz; Grzebinoga, Adam; Roguska, Barbara (Journal of Education, Health and Sport, 2025)
Thalidomide, despite its controversial history associated with teratogenic effects is currently used in the treatment of various conditions including oncological, immunological and dermatological diseases. The drug exhibits anti-inflammatory, immunomodulatory and anti-angiogenic effects, making it potentially effective in the treatment of various diseases. The mechanism of action is based on modulating the CRL4CRBN E3 ubiquitin ligase complex by binding to cereblon (CRBN), which leads to a change in the substrates recognized by this complex and the degradation of specific proteins. Thalidomide is used in the treatment of multiple myeloma, especially in cases resistant to other treatment methods. In addition, it can support the treatment of glioblastoma multiforme due to its anti-angiogenic and immunomodulatory effects. It is also used in the treatment of Crohn’s disease, systemic lupus erythematosus, and idiopathic pulmonary fibrosis (IPF). In Crohn’s disease it works by blocking TNF-α and modulating the immune response. In cutaneous lupus erythematosus it reduces inflammation, modulates the immune response and inhibits angiogenesis. In IPF, it inhibits the production of pro-inflammatory cytokines and reduces oxidative stress. The use of thalidomide is associated with a risk of teratogenicity, which requires strict control and the use of effective methods of contraception. In addition thalidomide can cause side effects, mainly hematological and gastrointestinal disorders. Due to the side effect profile, the use of thalidomide requires caution and close monitoring of the patient by a physician.